Knowledge And Interest Of Pregnant Mother Towards Pregnant Mother's Implementation - Rosda (Journal of Applied Nursing and Health, 2019)
Health development in Indonesia is still prioritized on efforts to improve the health status of mothers and children, especially in the most vulnerable groups of health, namely pregnant mother, mothers of birth, infants and the perinatal period. As a result or impact that will occur if maternal health decreases it will increase the incidence of mortality and morbidity in the mother and baby. Classes of pregnant mother have several advantages for pregnant mother, including material given thoroughly and planned in accordance with the guidelines, the time of discussion of material becomes effective because the presentation of material is well structured. Objective To find out the relationship between Knowledge and Interest in Pregnant mother Against the Implementation of Classes of Pregnant mother in the Wuasa-Poso Health Center Area. The design used in the study is correlation. Population is all pregnant mother during ANC visits in the Wuasa-Poso Health Center area. The sample size was 33 respondents using Accidental sampling technique. Independent variables of research are knowledge and interests. The dependent variable is implementation. Data was collected using a questionnaire, then the data were analyzed using the Spearment rho test with a significance level of α ≤ 0.05. The results showed that most respondents had enough knowledge as many as 18 respondents (54.5%), enough interest as many as 16 respondents (48.5%), implementing the implementation of the class of pregnant mother as many as 28 respondents (84.8%). The results obtained from the rho spearmen test with a <0.05 obtained p = 0,000 where H1 was accepted and H0 was rejected which means that there is a relationship between the relationship between Knowledge and Interest of Pregnant mother Against the Implementation of Classes of Pregnant mother in the Health Center of Wuasa-Poso There is a relationship between Knowledge and Interest in Pregnant mother Against the Implementation of Classes of Pregnant mother in the Wuasa-Poso Health Center Area.